Dysregulation of Regional Endogenous Opioid Function in Borderline Personality Disorder - Prossin, Alan R; Love, Tiffany M; Koeppe, Robert A; Zubieta, Jon-Kar; Silk, Kenneth R (American Journal of Psychiatry, 2010)
ObjectiveBorderline personality disorder is characterized by a lack of effective regulation of emotional responses. The authors investigated the role of the endogenous opioid system and μ-opioid receptors in emotion regulation in borderline personality disorder. MethodMu-opioid receptor availability in vivo (nondisplaceable binding potential, or BPND) was measured with positron emission tomography and the selective radiotracer [11C]carfentanil during neutral and sustained sadness states in 18 unmedicated female patients with borderline personality disorder and 14 healthy female comparison subjects. ResultsPatients showed greater regional μ-opioid BPND than did comparison subjects at baseline (neutral state) bilaterally in the orbitofrontal cortex, caudate, and nucleus accumbens and in the left amygdala, but lower BPND in the posterior thalamus. Sadness induction was associated with greater reductions in BPND (endogenous opioid system activation) in the patient group than in the comparison group in the pregenual anterior cingulate, left orbitofrontal cortex, left ventral pallidum, left amygdala, and left inferior temporal cortex. Patients showed evidence of endogenous opioid system deactivation in the left nucleus accumbens, the hypothalamus, and the right hippocampus/parahippocampus relative to comparison subjects. Correlations of baseline measures with the Dissociative Experiences Scale and endogenous opioid system activation with the Barratt Impulsiveness Scale did not remain significant after correction for multiple comparisons. ConclusionsDifferences exist between patients with borderline personality disorder and comparison subjects in baseline in vivo μ-opioid receptor concentrations and in the endogenous opioid system response to a negative emotional challenge that can be related to some of the clinical characteristics of patients with borderline personality disorder. The regional network involved is implicated in the representation and regulation of emotion and stress responses.